2017
DOI: 10.3389/fpsyt.2017.00172
|View full text |Cite
|
Sign up to set email alerts
|

Increased Subjective Distaste and Altered Insula Activity to Umami Tastant in Patients with Bulimia Nervosa

Abstract: The aim of this study was to examine differences in brain neural activation in response to monosodium glutamate (MSG), the representative component of umami, between patients with bulimia nervosa (BN) and healthy women (HW) controls. We analyzed brain activity after ingestion of an MSG solution using functional magnetic resonance imaging (fMRI) in a group of women with BN (n = 18) and a group of HW participants (n = 18). Both groups also provided a subjective assessment of the MSG solution via a numerical rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 74 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…Neuroimaging studies have shown anatomical alterations in women with eating disorders in brain regions centrally involved in taste and its valuation (e.g., medial orbitofrontal cortex, insula, striatum) [102]. Prior findings also suggest that women with acute restricting-type AN [103] and those recovered from AN or BN show aberrant anterior insula responses to sucralose [104,105]. Women with restricting-type AN display a reduced ability to discriminate between sucrose, artificial saliva, or no solution, compared to healthy women and to women recovered from AN [106].…”
Section: Tasting and Chewingmentioning
confidence: 99%
“…Neuroimaging studies have shown anatomical alterations in women with eating disorders in brain regions centrally involved in taste and its valuation (e.g., medial orbitofrontal cortex, insula, striatum) [102]. Prior findings also suggest that women with acute restricting-type AN [103] and those recovered from AN or BN show aberrant anterior insula responses to sucralose [104,105]. Women with restricting-type AN display a reduced ability to discriminate between sucrose, artificial saliva, or no solution, compared to healthy women and to women recovered from AN [106].…”
Section: Tasting and Chewingmentioning
confidence: 99%
“…83 In studies on binge eating, bitter taste led to higher medial prefrontal electroencephalography signal, or umami taste, more strongly activated the insula in BN, whereas hedonic ratings were lower. 84,85 Cognition During a reversal learning task involving positive and negative feedback, participants with AN changed behavior strategy more frequently after negative feedback, related to cingulate activation. 86 During the Wisconsin Card Sorting Test for cognitive flexibility, participants with AN had higher activation during behavior change in the frontal, parietal, and occipital regions but lower activation during learning or maintaining rulebased behavior.…”
Section: Perception and Interoceptionmentioning
confidence: 99%
“…Opposite to HC, they had a larger response to sucrose than to a bitter stimulus in the left dlPFC, brainstem, OFC, and right postcentral gyrus (Monteleone et al, 2017). But after giving an umami stimulus, patients with BN reported lower liking scores and displayed more activity of the right middle insula and ACC (Setsu et al, 2017). Of the four studies that used a reward task, there were two (50%) that used a MID or FID, one (25%) that used a reward‐guessing task, and one (25%) that used a spatial learning task where participants needed to navigate a maze in order to find rewards.…”
Section: Resultsmentioning
confidence: 99%
“…Opposite to HC, they had a larger response to sucrose than to a bitter stimulus in the left dlPFC, brainstem, OFC, and right postcentral gyrus (Monteleone et al, 2017). But after giving an umami stimulus, patients with BN reported lower liking scores and displayed more activity of the right middle insula and ACC (Setsu et al, 2017).…”
Section: Reward Responsivenessmentioning
confidence: 91%